ENHANCING THE QUALITY OF PHYSIOTHERAPY-REHABILITATION SERVICES AT XUYEN A GENERAL HOSPITAL, HO CHI MINH CITY IN 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: Assessing the current quality of physiotherapy-rehabilitation services in 2024-2025.Subjects and methods: A cross-sectional descriptive study using data from 14 hospital quality indicators and a satisfaction survey of 200 patients or patients’ relatives assessed using a Likert scale.Results: The results indicate that 5/14 department quality indicators remain low, including average hospital stay duration, number of incident reports. In terms of patient satisfaction, most aspects received high ratings (98.5%-100%), except for infrastructure (74%) and Wi-Fi access (79.5%).Conclusion: The results showed that 5 out of 14 indicators of the department were at a low level. Regarding satisfaction levels, the highest satisfaction was reported in the domains of information transparency and medical procedures, the attitudes and professional competence (100%). The lowest satisfaction was observed in the domain of facilities and service equipment (74%).
Keywords: Quality of medical examination and treatment services, Hospital quality, Patient satisfaction, Quality management